Tumor-Specific Low Molecular Weight Forms of Cyclin E Induce Genomic Instability and Resistance to p21, p27, and Antiestrogens in Breast Cancer - Akli, Said; Zheng, Ping-Ju; Multani, Asha S.; Wingate, Hannah F.; Pathak, Sen; Zhang, Ning; Tucker, Susan L.; Chang, Sandy; Keyomarsi, Khandan (Cancer research (Chicago, Ill.), 2004)
The deregulated expression of cyclin E as measured by the overexpression of its low molecular weight (LMW) isoforms is a powerful predictor of poor outcome in patients with breast cancer. The mechanism by which these LMW forms give tumor cells a growth advantage is not known and is the subject of this article. In this article, we provide the pathobiological mechanisms of how these LMW forms are involved in disease progression. Specifically, we show that overexpression of the LMW forms of cyclin E but not the full-length form in MCF-7 results in (a) their hyperactivity because of increased affinity for cdk2 and resistance to inhibition by the cyclin-dependent kinase inhibitors p21 and p27, (b) resistance to the growth inhibiting effects of antiestrogens, and (c) chromosomal instability. Lastly, tumors from breast cancer patients overexpressing the LMW forms of cyclin E are polyploid in nature and are resistant to endocrine therapy. Collectively, the biochemical and functional differences between the full-length and the LMW isoforms of cyclin E provide a molecular mechanism for the poor clinical outcome observed in breast cancer patients harboring tumors expressing high levels of the LMW forms of cyclin E. These properties of the LMW forms cyclin E suggest that they are not just surrogate markers of poor outcome but bona fide mediators of aggressive disease and potential therapeutic targets for patients whose tumors overexpress these forms.